2014
DOI: 10.1016/j.neuroscience.2014.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Common effects of fat, ethanol, and nicotine on enkephalin in discrete areas of the brain

Abstract: Fat, ethanol, and nicotine share a number of properties, including their ability to reinforce behavior and produce overconsumption. To test whether these substances act similarly on the same neuronal populations in specific brain areas mediating these behaviors, we administered the substances short-term, using the same methods and within the same experiment, and measured their effects, in areas of the hypothalamus (HYPO), amygdala (AMYG), and nucleus accumbens (NAc), on mRNA levels of the opioid peptide, enkep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…In a recent report, high-fat diet itself protected against stress-induced general anxiety- and depression-like behaviors (Finger et al, 2011). Fat, ethanol, and nicotine intake have been shown to increase the single- and double-labeling of the endogenous opioid peptide, enkephalin (ENK)- and c-Fos-immunoreactivity in precisely the same brain areas, the medial area of the paraventricular nucleus of the hypothalamus, central nucleus of the amygdala, and the core of the nucleus accumbens (Chang et al, 2014). These findings suggest that food rich in fat has effects in common with addictive drugs which are known to activate the same populations of ENK-expressing neurons in these nuclei of the hypothalamus and limbic system, thereby affecting behaviors such as social interaction, rewording seeking, and preference decision making.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, high-fat diet itself protected against stress-induced general anxiety- and depression-like behaviors (Finger et al, 2011). Fat, ethanol, and nicotine intake have been shown to increase the single- and double-labeling of the endogenous opioid peptide, enkephalin (ENK)- and c-Fos-immunoreactivity in precisely the same brain areas, the medial area of the paraventricular nucleus of the hypothalamus, central nucleus of the amygdala, and the core of the nucleus accumbens (Chang et al, 2014). These findings suggest that food rich in fat has effects in common with addictive drugs which are known to activate the same populations of ENK-expressing neurons in these nuclei of the hypothalamus and limbic system, thereby affecting behaviors such as social interaction, rewording seeking, and preference decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Both gene expression and peptide levels of ENK are increased in the PVN in response to moderate and excessive alcohol drinking (Chang et al, 2007; Oliva and Manzanares, 2007), and this effect occurs with as little as a single alcohol injection (Chang et al, 2007; de Gortari et al, 2000). Anatomical analysis has shown that the alcohol-induced transcriptional activation of ENK neurons specifically occurs in the medial parvocellular area of the PVN at all anterior-posterior levels (Chang et al, 2014). Therefore, just as with GAL, hypothalamic ENK not only endogenously promotes alcohol drinking, but the drinking of alcohol in turn increases the activity and levels of hypothalamic ENK, completing the positive feedback circuit.…”
Section: Neuropeptides With a Positive Feedback Relationship To Almentioning
confidence: 99%
“…The subcellular localization of DOPR within the BLA and CeA suggests that DOPR may function to inhibit the excitation of BLA and CeA neurons in the presence of a stressor (Herringa et al, 2004; Tye et al, 2011). The postsynaptic localization of DOPR is also supported by in situ hybridization and immunohistochemical data of enkephalin mRNA and immunoreactivity in the amygdalar complex including the BLA and CeA (Berube et al, 2013; Chang et al, 2014; Chieng et al, 2006; Zhang and McDonald, 2016). …”
Section: Discussionmentioning
confidence: 70%